Bounded Rationality and Socially Optimal Limits on Choice in a Self-Selection Model - Eytan Sheshinski (Center for Economic Studies and ifo Institute (CESifo), 2003)
When individuals choose from whatever alternatives available to them the one that maximizes their utility then it is always desirable that the government provide them with as many alternatives as possible. Individuals, however, do not always choose what is best for them and their mistakes may be exacerbated by the availability of options. We analyze self-selection models, when individuals know more about themselves than it is possible for governments to know, and show that it may be socially optimal to limit and sometimes to eliminate individual choice. As an example, we apply Luce's (1959) model of random choice to a work-retirement decision model and show that the optimal provision of choice is positively related to the degree of heterogeneity in the population and that even with very small degrees of non-rationality it may be optimal not to provide individuals any choice.
Keywords: 330; logit; self-selection; moral-hazard; retirement